Student’s Numerical Ability on Minimum Competency Assessment in Indonesia: Focusing on Data and Uncertainly Problems (Universitas Pendidikan Indonesia Kampus Cibiru, 2023)
This study aims to describe students' numeracy ability in solving math problems on data content and uncertainty based on the Minimum Competency Assessment (AKM) in terms of students' initial abilities at SMPN 1 Parepare. The subjects of the study were 6 students: 2 students with low initial ability, 2 students with medium initial ability, and 2 students with high initial ability. 6 subjects are grade IX students at SMPN 1 Parepare for the 2022/2023 school year. The results showed that (1) Students with low initial mathematical ability only met three numeracy indicators. Thus, students with a low initial mathematics ability category are at the competency level of